Aislamientos de endófitos en nódulos de alfalfa en haplustoles salinos - Gallace, Maria Eugenia; Vigna, Camila; Dalmasso, Lucas; Porta Siota, Fernando; Díaz-Zorita, Martín (Asociación Argentina de la Ciencia del Suelo, 2023)
Poster